2015
DOI: 10.1007/978-3-319-09864-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Interval Mappings for an Elliptic Bursting Model

Abstract: We employed Poincaré return mappings for a parameter interval to an exemplary elliptic bursting model, the FitzHugh-Nagumo-Rinzel model. Using the interval mappings, we were able to examine in detail the bifurcations that underlie the complex activity transitions between: tonic spiking and bursting, bursting and mixed-mode oscillations, and finally, mixed-mode oscillations and quiescence in the FitzHugh-Nagumo-Rinzel model. We illustrate the wealth of information, qualitative and quantitative, that was derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…Incorporating slow dynamics, it can exhibit a wide range of different firing patterns in certain parameter regimes. The FHR model was introduced by FitzHugh and Rinzel [28][29][30][31] and is also known as the elliptic bursting model 31 . It is described by the system of ordinary differential equations…”
Section: The Excitable Fhr Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporating slow dynamics, it can exhibit a wide range of different firing patterns in certain parameter regimes. The FHR model was introduced by FitzHugh and Rinzel [28][29][30][31] and is also known as the elliptic bursting model 31 . It is described by the system of ordinary differential equations…”
Section: The Excitable Fhr Modelmentioning
confidence: 99%
“…The decrease of a and c gives rise to longer intervals between consecutive bursting activities, with the system showing relatively fixed times in burst duration. Additionally, with the increase of a, the interburst intervals become shorter and the oscillations change to tonic spiking 28,31 . In our work, we have used δ = 0.08, a = 0.7, b = 0.8, µ = 0.002, c = −0.775 and we will be varying I.…”
Section: The Excitable Fhr Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchronization conditions in a network in which the central element modeling the pacemaking neuron is linked to the group of uncoupled neurons were presented. Using the Poincaré return mappings, the authors of [14] were able to examine in detail the bifurcations that underlie the complex activity transitions between: tonic spiking and bursting, bursting and mixed-mode oscillations, and finally, mixed-mode oscillations and quiescence in the FR model. This paper is devoted to clarifying the analytical properties of the FR model.…”
Section: Introductionmentioning
confidence: 99%
“…A whole CPG can be also multifunctional if it governs more than one behavior, in contrast to a dedicated CPG which is arranged for the purpose of a single locomotion. Modeling studies, mathematical and computational, have proven to be useful for gaining insights into operational principles of CPGs [8][9][10][11][12][13], in particular, multifunctional ones [14][15][16]. This study has been inspired by recent experimental studies of neuronal activity patterns recorded from the identified interneurons of a [dedicated] CPG governing the swim pattern of a sea slug Melibe leonina [17][18][19] and possible consequences of understanding neurological phenomena in general.…”
Section: Introductionmentioning
confidence: 99%